Relationship Between Muscle Strength, Body Composition and Bone Mineral Density in Adolescents - Pelegrini, Andreia (2022)
Adolescence is an important period for the acquisition of bone mass, which can be enhanced by several factors. This study aimed examine the relationships of handgrip strength, free-fat mass, and fat mass with bone mineral density in adolescents. 118 adolescents (60 girls), aged 10 to 14 years, participated in the study. Information on sex, age, handgrip strength, free-fat mass, fat mass and bone mineral density were collected. Multiple linear regression analyses were conducted to examine possible relationships between bone mineral density and handgrip strength, free-fat mass and fat mass. There was a relation between handgrip strength and free-fat mass with bone mineral density in both sexes. Fat mass was correlated with bone mineral density only in girls (r= 0.314, p< 0.014). The final models, adjusted for sexual maturation, included free-fat mass (girls - β= 0.419, p< 0.001; boys - β= 0.455; p< 0.001) and handgrip strength (girls - β= 0.358, p< 0.05; boys - β= 0.325; p< 0.05) and these variables together explained 51.8% and 62.9% of the variation of bone mineral density, in girls and boys, respectively. Handgrip strength and free-fat mass were positively associated with bone mineral density. A sex-specific difference indicated that higher levels of free-fat mass are of paramount importance for both sexes.